Adjectivised, substantivised forms of participles in Diwani Lughat-at-Turk by M. Kashgari - Akzhigitova А.О.; Sarsenbay Ж.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
Ancient and Medieval Turkic monuments occupy a unique position in the study of the historical processes of the formation and development of the Kazakh language. The study and analysis of linguistic forms in M. Kashgari’s Diwani Lughat at-Turk represents a significant and pressing research objective in the present era. Despite extensive research into this work from literary and historical perspectives, there is still a paucity of linguistic and theoretical analysis of Kazakh linguistics. Accordingly, this article examines the participles, including their adjectivised and substantivised forms in M. Kashgari’s Dictionary. This topic is being considered for the first time in the field of Kazakh linguistics. The principal objective of this article is to examine the participles in the Dictionary by M. Kashgari, regarded as a Medieval Turkic written monument, in order to ascertain their substantive and qualitative meanings, as well as the ways in which they are used. In order to achieve this aim, the article presents a systematic classification of the groups of participles used in the 11th century, based on historical grammar, and identifies their predicative and attributive meanings. The article employs the Turkic Dictionary by M. Kashgari (translated by A. Yegeubai) as its principal source, while also considering the theoretical conclusions and interpretations of domestic and foreign scientists. The findings of the study contribute to the examination of Medieval Turkic written monuments and the history of the Kazakh language. Furthermore, these findings will prove invaluable to those engaged in historical grammar and Kazakh word formation research.